Genome-wide DNA methylation analysis reveals a prognostic classifier for non-metastatic colorectal cancer (ProMCol classifier). Issue 1 (3rd November 2017) - Gündert, Melanie; Edelmann, Dominic; Benner, Axel; Jansen, Lina; Jia, Min; Walter, Viola; Knebel, Phillip; Herpel, Esther; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann; Burwinkel, Barbara
Abstract : Objective: Pathological staging used for the prediction of patient survival in colorectal cancer (CRC) provides only limited information. Design: Here, a genome-wide study of DNA methylation was conducted for two cohorts of patients with non-metastatic CRC (screening cohort (n=572) and validation cohort (n=274)). A variable screening for prognostic CpG sites was performed in the screening cohort using marginal testing based on a Cox model and subsequent adjustment of the p-values via independent hypothesis weighting using the methylation difference between 34 pairs of tumour and normal mucosa tissue as auxiliary covariate. From the 1000 CpG sites with the smallest adjusted p-value, 20 CpG sites with the smallest Brier score for overall survival (OS) were selected. Applying principal component analysis, we derived a prognostic methylation-based classifier for patients with non-metastatic CRC (ProMCol classifier). Results: This classifier was associated with OS in the screening (HR 0.51, 95% CI 0.41 to 0.63, p=6.2E−10) and the validation cohort (HR 0.61, 95% CI 0.45 to 0.82, p=0.001). The independent validation of the ProMCol classifier revealed a reduction of the prediction error for 3-year OS from 0.127, calculated only with standard clinical variables, to 0.120 combining the clinical variables with the classifier and for 4-year OS from 0.153 to 0.140. All results were confirmed for disease-specific survival. Conclusion: The ProMCol classifier could improve the prognostic accuracy for patients with non-metastatic CRC.